Modern Islam, Politics, and the Making of Religious Commodification Among Female Members of Majelis Taklim Circle in Bandar Lampung, Indonesia - Mulyadi, Mulyadi; Jauhari, Tontowi; Hidayat, Mansur; Sugiono, Arif (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
Despite the common belief in society about the declining fate of religion in time of modernity, everyday behaviors of religious societies have shown that religion has been increasingly commodified for political purposes. This article aims to study the ways in which modernity has enabled the dynamic use of religious commodification in political sectors. Its main question is how political leaders have used religious doctrines, values, and symbols for gaining their electoral supports. Data of this research is collected through surveys among female Muslim members of Islamic learning circles (majelis taklim) in Bandar Lampung, the biggest city in the province of Lampung, where religious learning circles have increasingly flourished in the last few years. This research finds out ample evidence showing the significant influences of modernization and commodification of religion in determining political behaviors of the female members of Islamic learning circles. Modernization in the context of this research is defined as knowledge, urbanization, increased income, technological progress, social norms, social interaction, social institutions, and commodification of religion is identified as the acts of making religious teachings and activities as a commodity, empirically manifested in the form of transforming social relations into economic relations (relation oriented for economic interests, materialization of a thing spiritual).